THE CONTENT OF ORGANIC MATTER IN WATER AND SEDIMENTS IN COASTAL WATER MIRROR DISTRICTS SERDANG BEDAGAI NORTHERN SUMATERA PROVINCE - Sihaloho, Elpon; Nedi, Syahril; Nurrachmi, Irvina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Organic matter is one indicator of environmental fertility either on land or at sea. Content Organic matter in the waters will experience an increase caused by discharges from households, agriculture, industry and organic waste from land to coast. The objective of this research is to know the input of organic material entering the waters of Cermin Beach and to know the content of organic material in water and sediment in the waters of Coast Mirror and the relation of organic matter content to water and sediment. The result of calculation of organic matter content in water ranged from 14,19 - 34,76 mg / l and the content of organic matter in sediment ranged from 0,33 - 8,90%. Furthermore, through simple linear regression test known that the relationship of organic matter content in water and sediment has a weak relationship with the correlation r = 0.137. The analysis of sedimentary fractions in the Coastal waters of Mirror is dominated by sandy substrates. Key Words : Organic Matter, sediment, Water Of Mirror